Early Return Of Activity Of Daily Living After Surgery Of Pfna Li Fixation In Elderly Osteoporotic Intertrochanteric - M.Nouri, Mohammed Hazim (AL-Kindy College Medical Journal, 2019)
Background:    Hip fractures are common, morbid, and costly health events that threaten independence and function of older patients . Early functional recovery is extremely important for elderly patients with femoral intertrochanteric fractures to shorten their hospital stay, omit the necessity of the further nursing and care services, and reduce associated medical expenditures . Assessment of  (ADL) is an important predictor of outcomes Of orthopedic surgery in very early postoperative period at two weeks and a month postoperatively using Japanese orthopedic score get a quick recovery of ADL & return the patient to his or her premorbid level function reducing the morbidity and mortality.Objectives: We evaluate in our study the Return of ADL function in 27 cases of elderly with intertrochanteric hip fractures treated with closed reduction and surgical  fixation with proximal femoral nail anti rotation in very early postoperative period at two weeks and a month postoperatively.Type of the study : Prospective observational studMethods: Prospective observational study of 27 consecutively patients with an intertrochanteric fracture Stable and unstable  fractures treated between December 2015 and Augest 2016 were enrolled in study.Results: Regain in a walking ability and daily living activities which indicate a fast recovery in early days and weeks after surgery in contrary the regular fellow up a month up to 3 month revealed a slower recovery from that achieved in early weeksConclusions: Use of proximal femoral nailing in intertrochanteric elderly osteoporostic fracture has a significant impact on early functional recovery